Internal tandem flexible and compressible electrochemical capacitor based on polypyrrole/carbon fibers. (10th December 2017) - Chang, Yahui; Han, Gaoyi; Xiao, Yaoming; Chang, Yunzhen; Song, Hua; Li, Miaoyu; Li, Yanping; Zhang, Ying
Graphical abstract: Highlights: Carbon fibers embedded in sponge used as electrode to deposit polypyrrole (PPy/CFs). Internal tandem capacitor was obtained by alternately cutting and insulating PPy/CFs. The output voltage of single device can reach to 3.0 V and can turn on a LED Abstract: Polypyrrole (PPy) doped with phosphate ions has been electrochemically deposited on the carbon fibers (CFs) embedded in melamine sponge (MS) to obtain the flexible integrated electrochemical capacitors' (ECs) electrodes (PPy-CFs/MS/PPy-CFs). The ECs prepared from the PPy-CFs/MS/PPy-CFs based on H3 PO4 /polyvinyl alcohol (PVA) gel electrolyte exhibit good performance and excellent cyclic stability. In order to get high output potential difference in single EC device with aqueous electrolyte, the devices with internal tandem structure have been fabricated through alternately dividing and insulating the PPy-CFs electrodes embedded in MS. The measurements of cyclic voltammetry and galvanostatic charge/discharge reveal that the devices containing two, three, four and five ECs internally connected in series have a good electric relationship, and single device containing five internal tandem ECs can easily achieve 3.0 V output potential difference and light up a light emitting diode. Furthermore, under compressing, bending and twisting conditions, the performances of the devices are almost unchanged compared with those under normal state. This method will open a new strategy to fabricate flexible and compressible energy storage devices with relatively high voltage output and compact structure.